Theoretical Investigations on utilization of alternative fuels in an IDI diesel engine under dual fuel mode - Ahmad, Nafis; Al Khamis , Nawaf (Journal of King Abdulaziz University: Engineering Sciences, 2023)
The study explores the impact of ammonia and DME on the combustion / performance characteristics and exhaust emissions of a dual-mode IDI diesel engine without making any major alterations to the engine. Fortran-77 programming is used to develop a computer simulation program. The findings show that blending in dual mode raises pre and main chamber temperatures and pressures, as well as IMEP and BP, but lowers BSEC as ammonia substitution increases from 5% to 25%. Blending (diesel + ammonia) increases BP by 15.93 percent, 37.25 percent, and 72.42 percent in dual mode at 20%, 40%, and 60% NG substitutions respectively and blending (diesel + DME) increases BP by 17.79 percent, 40.17 percent, and 76.99 percent in dual mode at 20%, 40%, and 60% NG substitutions respectively